Types of CEO Owner, Professional CEO, and CEO Gender Diversity in Earnings Management - Maria Dewanti Timbo; Wijaya Triwacananingrum (Universitas Pelita Harapan, 2024)
This research was conducted with the aim of finding out whether there is an influence of the type of CEO Owner, CEO Professional, and CEO gender on earnings management practices. The research was conducted on companies listed on the Indonesia Stock Exchange (BEI) in the period 2020 to 2022, by excluding companies operating in the financial industry. The authors used secondary data in this research, namely in the form of company financial reports for the 2020-2022 period obtained from S&P Capital IQ, company annual reports obtained from the IDX website and the company's official website. The number of samples in this research was 60 companies registered on the IDX using a data analysis technique, namely multiple linear regression. The research results show that CEO owners do not have a significant influence on earnings management compared to professional CEOs, and male CEOs do not have a significant influence on earnings management compared to female CEOs.